Analysis Of Customer Satisfaction With Packaged Drinking Water Products Using Service Quality (SERVQUAL) And Importance Performance Analysis (IPA) Methods - Maulana, Muhammad Helmi; Nuruddin, Moch. (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
PT. XYZ is a bottled mineral water manufacturer in Gresik, striving to deliver customer satisfaction and stay competitive. This study aims to quantify consumer satisfaction with PT. XYZ's product quality. We collected data through a questionnaire and analyzed it using the Servqual method and Importance Performance Analysis (IPA). The questionnaire included nine quality attributes, categorized into five dimensions. IPA was utilized to prioritize service quality attributes. The Servqual method revealed a negative gap, indicating suboptimal service. The Cartesian IPA diagram highlighted two critical areas for improvement: enhancing staff interaction during service and improving personnel demeanor, specifically their politeness, and friendliness. These improvements are vital as they align with consumer expectations and are essential for enhancing overall service quality at PT. XYZ. Keywords: Service Quality, Importance Performance Analysis (IPA), SERVQUAL